The effect of the using Prior & Acquired Knowledge Strategy on Achievement in Science and Reflective Thinking among Seventh Graders in UNRWA School - Ayesh, Eman Ahmad (Journal of Educational and Psychological Sciences, 2023)
The purpose of this study aimed at investie the effect of the using Prior & Acquired Knowledge Strategy on Achievement in Science and Reflective Thinking among Seventh Graders in UNRWA School with the traditional method, The study attempted to answer the main question: What is the effect of the using Prior & Acquired Knowledge Strategy on Achievement in Science and Reflective Thinking among 7th Graders. To answer the questions of the study and test its hypotheses, the study used the experimental method. with quasi-experimental disign by applying the study to a sample of (86) female students of the Seventh in the basic first school of girls in UNRWA Schools in the district of Jenin, " Transition movement and Newton’s laws of motion "from the Science book in two groups (experimental and control), in the first semester of the year (2017/2018). To actualize the purpose of the study, the researcher used the following Achievement test, the Reflective Thinking test, and the teacher guide were prepared for the experimental group. The results of the study showed that there are statistically difference between the means of graders in the Achievement due to method of teaching in favor of the experimental group. There was also a statistically difference between the means of graders in the Reflective Thinking due to method of teaching in favor of the experimental group. Based on the results, the study recommended the following the important of using the strategy KWL of teaching of Science because its the impact on the achievement of students, as well as the students’ positive attitudes towards their use in learning.